Escribir al femenino Colette y Annie Ernaux. El retorno a la madre - Zenarruza de Clément, Silvia (Universidad Nacional del Litoral, 2015)
The article suggests the comparative Reading of Colette and Annie Ernaux about a topic that inspires both of them to write. In spite of the temporal distance and difference in styles that separate them we can hypothesize that both authors, through these texts, carry out a work of repair of a main character recovery of their own lives, which come to settle inner conflicts.